Multimodal Screening for Pulmonary Arterial Hypertension in Systemic Scleroderma: Current Methods and Future Directions - Ioan Teodor Dragoi; Ciprian Rezus; Alexandra Maria Burlui; Ioana Bratoiu; Elena Rezus (Medicina, 2024)
Systemic sclerosis (SSc) is an immuno-inflammatory rheumatic disease that can affect both the skin and internal organs through fibrosis. Pulmonary arterial hypertension (PAH) is one of the most severe secondary complications. Structural changes in the vascular bed lead to increased pressures in the pulmonary circulation, severely impacting the right heart and significantly affecting mortality. The gold standard for diagnosing PAH is right heart catheterization (RHC), an invasive method for measuring cardiac pressure. Due to the high risk of complications, procedural difficulties, and significant costs, non-invasive screening for SSc-PAH has garnered significant interest. Echocardiography is likely the most important screening tool, providing structural and functional information about the right heart through measurements that have proven their utility over time. In addition to imagistic investigations, serum biomarkers aid in identifying patients at risk for PAH and can provide prognostic information. Currently, well-known serum biomarkers (NT-proBNP, uric acid) are used in screening; however, in recent years, researchers have highlighted new biomarkers that can enhance diagnostic accuracy for SSc patients. Pulmonary involvement can also be assessed through pulmonary function tests, which, using established thresholds, can provide additional information and help select patients requiring RHC. In conclusion, given the invasiveness of RHC, non-invasive screening methods are particularly important for SSc patients.